Pengaruh Strategi Pembelajaran Active Knowledge Sharing Terhadap Hasil Belajar Pada Mata KuliahBiologi Dan Genetika Manusia Mahasiswa D3 Perekam Medik Dan Informatika Kesehatan Tahun Akademik 2016/2017: Active Knowledge Sharing, Hasil belajar Biologi, Ranah Afektif, Konitif dan Psikomotorik. - Ria Fajar Nurhastuti (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2017)
Background of the study : The purpose of this research was to know the effect of applicting teaching strategy ”Active Knowledge Sharing” to the achievement of lecture “ Biologi dan Genetika Manusia” for students of D3 Medical recorder and health informatics in the Academic year of 2016/2017.Purpose : This research was include in experimental design with quantitative approach. Design of research was “Posttest Only Control Group Design” with applicating teaching strategy “Active Knowledge Sharing “ on experiment group and conventional teaching on control group. Reseach population was all of student D3 Medical recorder and health informatics academic year of of 2016/2017. Sample technique was use Purposive Sampling, so took students of the first semester as an object of research. Collecting data technique was use multiple choice test, essay test, observation paper, and school documentation. To exam the hypothesis was using T-test. Conclusion : Result of this research was teaching strategy “Active Knowledge Sharing” directly affecting on the achievement of affective, kognitive, and psikomotor of the students in the first semester D3 Medical recorder and health informatics STIKES Buana Husada Ponorogo.